IMF Staff papers : Volume 5 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1957)
As a part of the proceedings of the Eleventh Annual Meeting of the Board of Governors of the International Monetary Fund, an Informal Session on 'Recent Developments in Monetary Analysis' was held on September 25, 1956. The three papers which were presented at that Session by Dr. M. W. Holtrop, President of De Nederlandsche Bank, Dr. Paolo Baffi, Economic Adviser to Banca d'Italia, and Dr. Ralph A. Young, Director of the Division of Research and Statistics, Board of Governors of the Federal Reserve System, are reproduced below, together with the background paper, 'Monetary Analyses,' prepared by the Statistics Division of the Research and Statistics Department of the International Monetary Fund.